2008
DOI: 10.1007/s00068-008-8161-2
|View full text |Cite
|
Sign up to set email alerts
|

Low probability of Significant Intra-Abdominal Injury in Stable Patients with Abdominal ‘‘Seat Belt Sign’’

Abstract: Despite the widely accepted view that patients with an abdominal seat belt sign are more likely to have serious intraabdominal injuries, the results of our investigation showed no such association in a group of hemodynamically stable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, not all patients with IAI have AWE 6,8,10,23 and some studies report no increased risk of IAI in patients with AWE. 24,25 In this study, 22% of patients with IAI had no AWE noted in their chart. TLICS can be a valuable tool in patients without AWE to indicate risk of concomitant IAI; however, even in patients with AWEs, this study demonstrates that combining TLICS and AWE is a stronger predictor of concomitant IAI than AWE alone.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, not all patients with IAI have AWE 6,8,10,23 and some studies report no increased risk of IAI in patients with AWE. 24,25 In this study, 22% of patients with IAI had no AWE noted in their chart. TLICS can be a valuable tool in patients without AWE to indicate risk of concomitant IAI; however, even in patients with AWEs, this study demonstrates that combining TLICS and AWE is a stronger predictor of concomitant IAI than AWE alone.…”
Section: Discussionmentioning
confidence: 57%
“…While a physical exam may reveal concerning signs, children with IAI caused by blunt trauma, especially hollow viscous injuries, may have subtle, equivocal, or absent physical exam findings. 6,8,[23][24][25] Furthermore, if the patient has significant associated traumatic head injury and neurologic compromise, clinical examination and feedback may be limited. FAST (Focused Assessment with Sonography in Trauma) exams have shown to have mixed utility in identifying solid organ injury, are unable to identify hollow viscous injuries, and are not consistently used in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In another large multicenter prospective study, SBS has been confirmed to be independently associated with intraabdominal injuries (5). On the other hand, a few reports revealed that SBS is not significantly associated with higher risk of intestinal injury (10,11). However, it should be kept in mind that SBS causes direct trauma to the abdominal wall muscles which may be seen concurrently with intra-abdominal injuries.…”
Section: Discussionmentioning
confidence: 94%
“…Doersch and Dozier described a characteristic compression scar as a sign to suspect seat belt syndrome, and called it the “SBS” 7 . SBS refers to subcutaneous hemorrhagic spots consistent with the belt site and is associated with intra-abdominal organ damage 17 , although there may be no associated injury even when SBS is present 18 . Johnson and Eastridge reported that if the SBS is superior to the ASIS, there is an increased risk of intra-abdominal injury and abdominal surgery, and if the SBS is inferior to the ASIS, there is an increased risk of pelvic fracture, which is an indication and predictor of abdominal surgery 19 .…”
Section: Discussionmentioning
confidence: 99%